Analisis Proses Electrical Discharge Machining (EDM) Terhadap Keausan Elektroda Dengan Metode Taguchi - Yudi Oktriadi (Politeknik Manufaktur Negeri Bangka Belitung, 2020)
Different electrode materials give big influence on the machining process. Some electrode will eliminate workpiece efficiently but that give a high wear of electrode, the others electrode have a low wear but ability to eliminate materials of workpieces are very low. Taguchi Method is method in engineering to improves the process of different workpiece characteristics and can reduce the cost and resources to a minimum. In this study, the experimental design used is the experimental design of Taguchi with Orthogonal Array design, analysis Signal to Noise Ratio to determine the factors that affect the wear of electrodes, and analysis of variance. The results of the discussion on the analysis of the Taguchi experimental design method in Process Parameters Using EDM In Identifying Electrode Wear is obtained decisive steps orthogonal matrix, analysis of the characteristics of the proposed design smaller the better quality types to determine the value of SNR, determine the value of the effect of each replication in each of the factors that affect the wear of electrodes, Variance analysis performed to interpret the experimental data to determine the EDM process parameters electrodes Optimum wear.